Pregunta
upstudy study bank question image url

If \( \sqrt{2} \tan \alpha+1=0 \) and \( \cos \alpha>0 \), determine without the use of a calculator and with the of a diagram the value of: \( \begin{array}{ll}\text { (1) } \sqrt{3} \sin \alpha-\frac{\sqrt{2}}{\cos \alpha} & \text { (2) } \frac{1}{\cos ^{2} \alpha}+\tan ^{2} \alpha\end{array} \)

Ask by Chandler Lyons. in South Africa
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

sin α = –1/√3 and cos α = √(2/3). Expression (1): √3 sin α – (√2)/(cos α) = –1 – √3. Expression (2): 1/(cos²α) + tan²α = 2.

Solución

We begin with the equation   √2 · tan α + 1 = 0. Step 1. Solve for tan α.   √2 · tan α = –1  ⟹  tan α = –1/√2. Since tan α = sin α/cos α and we are given that cos α > 0, for tan α to be negative we must have sin α < 0. Thus, α is an angle in the fourth quadrant. Step 2. Express sin α in terms of cos α. We have   tan α = –1/√2 = sin α/cos α  ⟹  sin α = –(1/√2) cos α. Step 3. Use the Pythagorean identity sin²α + cos²α = 1. Substitute sin α = –(1/√2)cos α:   [–(1/√2) cos α]² + cos²α = 1   (1/2) cos²α + cos²α = 1   (3/2) cos²α = 1  ⟹  cos²α = 2/3. Since cos α > 0, take the positive square root:   cos α = √(2/3). Then, compute sin α:   sin α = –(1/√2) · √(2/3) = –√(2/3)⁄√2 = –√( (2/3)⁄2 ) = –√(1/3) = –1/√3. A quick check verifies that   (sin α)² + (cos α)² = (1/3) + (2/3) = 1. Now we have:   sin α = –1/√3  and  cos α = √(2/3). Step 4. Evaluate Expression (1).   Expression (1): √3 · sin α – (√2)/(cos α). Substitute the known values:   √3 · (–1/√3) – (√2)/(√(2/3))    = –1 – (√2)/(√(2/3)). Simplify the fraction:   (√2)/(√(2/3)) = √2 / (√2/√3)  (since √(2/3) = √2/√3)    = √2 · (√3/√2) = √3. Thus, Expression (1) becomes:   –1 – √3. Step 5. Evaluate Expression (2).   Expression (2): 1/(cos²α) + tan²α. We already have cos²α = 2/3 and tan α = –1/√2 so that tan²α = 1/2. Therefore,   1/(cos²α) = 1/(2/3) = 3/2,   tan²α = 1/2. Thus, Expression (2) becomes:   3/2 + 1/2 = 4/2 = 2. Final Answers:   (1) √3 sin α – (√2)/(cos α) = –1 – √3   (2) 1/cos²α + tan²α = 2 A diagram of the right triangle corresponding to α in the fourth quadrant can be drawn where the horizontal side is the adjacent side, the vertical side (taken as negative) is the opposite side, and the hypotenuse is positive. In this triangle, tan α = (opposite)/(adjacent) = –1/√2, which leads consistently to the values obtained for sin α and cos α.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the given equation \( \sqrt{2} \tan \alpha + 1 = 0 \), we isolate \(\tan \alpha\): \[ \tan \alpha = -\frac{1}{\sqrt{2}} \] Since \(\cos \alpha > 0\), \(\alpha\) must lie in the fourth quadrant (where \(\tan\) is negative). To find \(\sin \alpha\) and \(\cos \alpha\), we can use the identity \(\tan \alpha = \frac{\sin \alpha}{\cos \alpha}\), leading to: \[ \sin \alpha = -\frac{1}{\sqrt{2}} \cos \alpha \] Recall the Pythagorean identity \(\sin^2 \alpha + \cos^2 \alpha = 1\). Substituting \(\sin \alpha\) yields: \[ \left(-\frac{1}{\sqrt{2}} \cos \alpha\right)^2 + \cos^2 \alpha = 1 \] \[ \frac{1}{2} \cos^2 \alpha + \cos^2 \alpha = 1 \] \[ \frac{3}{2} \cos^2 \alpha = 1 \implies \cos^2 \alpha = \frac{2}{3} \] Thus, \(\cos \alpha = \sqrt{\frac{2}{3}} = \frac{\sqrt{6}}{3}\) (since \(\cos \alpha > 0\)). Now, substituting \(\cos \alpha\) back to find \(\sin \alpha\): \[ \sin \alpha = -\frac{1}{\sqrt{2}} \cdot \frac{\sqrt{6}}{3} = -\frac{\sqrt{6}}{3\sqrt{2}} = -\frac{\sqrt{3}}{3} \] Next, we can compute the two requested expressions: 1) For \( \sqrt{3} \sin \alpha - \frac{\sqrt{2}}{\cos \alpha} \): \[ \sqrt{3} \sin \alpha = \sqrt{3}\left(-\frac{\sqrt{3}}{3}\right) = -1 \] \[ \frac{\sqrt{2}}{\cos \alpha} = \frac{\sqrt{2}}{\frac{\sqrt{6}}{3}} = \frac{3\sqrt{2}}{\sqrt{6}} = \frac{3\sqrt{2} \cdot \sqrt{6}}{6} = \frac{3\sqrt{12}}{6} = \frac{\sqrt{12}}{2} = \frac{2\sqrt{3}}{2} = \sqrt{3} \] \[ \sqrt{3} \sin \alpha - \frac{\sqrt{2}}{\cos \alpha} = -1 - \sqrt{3} = - (1 + \sqrt{3}) \] 2) For \( \frac{1}{\cos^2 \alpha} + \tan^2 \alpha \): \[ \frac{1}{\cos^2 \alpha} = \frac{1}{\frac{2}{3}} = \frac{3}{2} \] \[ \tan^2 \alpha = \left(-\frac{1}{\sqrt{2}}\right)^2 = \frac{1}{2} \] \[ \frac{1}{\cos^2 \alpha} + \tan^2 \alpha = \frac{3}{2} + \frac{1}{2} = 2 \] Thus, the final values are: \[ \text{(1) } - (1 + \sqrt{3}), \quad \text{(2) } 2 \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad